Tools For Measuring Patient Safety Culture In Hospitals - Tarun Thukral; Dr. Meenakshi (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Patient safety culture is described as employees' shared values, attitudes, and behaviors in a healthcare organization. With increasing awareness of Organisational safety culture, hospitals continually strive to improve patient safety and quality. It entails the requirement of assessment tools focused on the cultural aspects of patient safety improvement efforts. The assessment of patient safety culture in the healthcare environment is mainly carried out through surveys or self-assessment tools, formed to perceive the attitude of healthcare professionals in hospitals. This review highlights different assessment tools available with their current and potential uses. Several assessment tools have been developed over the past, but awareness of the characteristics of different tools helps to select the appropriate tool suited for the organization under their circumstances. The appropriate tool depends upon the reliability of the tool for its culture, target population etc and there is a variety of tools being utilized for measuring Patient Safety Culture: Team Dimensions Rating Form (TDRF) Safety Attitude Questionnaire (SAQ) Oxford Non-Technical Skills Measure (NOTECHS) Observational Clinical Human Reliability Assessment (QCHRA) Non-Operative Procedure Errors (NOPE) Perceived Collaboration & Satisfaction About Care Decisions (CSACD) Anaesthetists Non-Technical Skills (ANTS) System And their overall aim and main goal is to improve patient safety and elevate quality care.